PENGARUH MOTIVASI KERJA APARATUR DAN KEMAMPUAN APARATUR TERHADAP KINERJA PELAYANAN PEMBUATAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SEMARANG - Kurnia Nur Aziizah; Titik Djumiarti (Journal of Public Policy and Management Review, 2020)
Population administration services as a compulsory service, given the population data can be obtained from the service that is used as material for policy making in the development of a region. The substance of population administration is in the form of population registration and civil registration, one of which is the birth certificate. The data shows the realization of the birth certificate ownership that has not yet reached it is target. This assumption is caused by the civil servants work motivation and civil servants ability on the performance of Birth Certificates making services in the Population and Civil Registry Office of Semarang Regency. This study uses a quantitative approach. Data collection techniques used in this study used a questionnaire with 51 respondents. Then the method used for data analysis is multiple linear regression analysis. The results showed that there was an influence between the civil servants work motivation and civil servants ability on the performance of the birth certificate making services in the Population and Civil Registry Office of Semarang Regency.